Further refinements of a continuous radon monitor for surface ocean water measurements - Li, Chunqian; Zhao, Shibin; Zhang, Chenglun; Li, Meng; Guo, Jinjia; Dimova, Natasha T.; Yang, Tong; Liu, Wen; Chen, Guangquan; Yu, Huaming; Xu, Bochao (Frontiers in Marine Science, 2022)
Radon is an excellent natural tracer for studying various geophysical processes. In the past centuries, radon isotopes measurement approaches for marine research have been fully developed but still suffer limitations. Here we present the setup and validation of an improved continuous online measurement system (PIC-ORn) to measure dissolved radon in the surface ocean and other water bodies. We demonstrated that the PIC measurement efficiency is ~2 times higher than a RAD7 and is less affected by relative humidity and produces reliable results. Laboratorial measurements indicated that the new PIC-ORn system responded timely to the change of radon activities in water. The new system was successfully deployed during a cruise to the northwest Pacific Ocean in June 2021. Despite low radon-in-water activities, the results obtained by the new PIC-ORn system matched the traditional measurement systems within the estimated uncertainties. The PIC-ORn detector takes advantage of higher efficiency, lower cost, and power consumption, and is less affected by air moisture. The new system does not rely on drying units, further reducing on-site supervision, which would benefit the researches in submarine groundwater advection and diffusion and ocean-atmosphere gas exchange.